Encountering Asian new horizon contesting and negotiating in fluid transitions : the work of the 2012-2013 API fellows - Nippon Foundation Fellowships for Asian Public Intellectuals; Chulalongkorn University. Institute of Asian Studies. API Regional Coordinating Institution (Nippon Foundation API Regional Coordinating Institution, Institute of Asian Studies, Chulalongkorn University, 2015)
The 20 papers that comprise this volume cover key areas such as gender and unique differences; cultural identity and shifting boundaries; local existance in global transitions; policy making for social justice; and natural disasters.